Inflationary performance in a monetary union with large wage setters - Lilia Cavallari (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2001)
Building on a micro-founded model of a two region-world economy in the tradition of the new open economy literature, this paper analyses the strategic interaction of large wage-setters and the central bank when switching from a regime of uncoordinated national monetary policies to a monetary union. The establishment of a monetary union is shown to favour wage restraint, provided the uni…ed central bank is not too conservative. Wage discipline may reduce equilibrium ination in a monetary union relative to the one under uncoordinated national monetary policies when wage setting is centralised across member countries.
Keywords: E5; F4; 330; monetary union; wage bargaining; inflationary bias; Währungsunion; Inflation; Lohnverhandlungstheorie; Geldpolitik; Internationale wirtschaftspolitische Koordination